2021
DOI: 10.1371/journal.pone.0245531
|View full text |Cite|
|
Sign up to set email alerts
|

Untangling the complexity of market competition in consumer goods—A complex Hilbert PCA analysis

Abstract: Today’s consumer goods markets are rapidly evolving with significant growth in the number of information media as well as the number of competitive products. In this environment, obtaining a quantitative grasp of heterogeneous interactions of firms and customers, which have attracted interest of management scientists and economists, requires the analysis of extremely high-dimensional data. Existing approaches in quantitative research could not handle such data without any reliable prior knowledge nor strong as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…This research takes smart bracelets among smart wearable products as a case study, and develops a research framework based on relevant literature, as shown in Fig. 1 [26,27,28]. The research process is mainly divided into two stages: the first stage involves semantic analysis to acquire demand information, while the second stage uses KANO analysis to classify demands and finally summarizes applicable design strategies based on demand classification characteristics.…”
Section: Research Frameworkmentioning
confidence: 99%
“…This research takes smart bracelets among smart wearable products as a case study, and develops a research framework based on relevant literature, as shown in Fig. 1 [26,27,28]. The research process is mainly divided into two stages: the first stage involves semantic analysis to acquire demand information, while the second stage uses KANO analysis to classify demands and finally summarizes applicable design strategies based on demand classification characteristics.…”
Section: Research Frameworkmentioning
confidence: 99%
“…Fast home delivery, convenience, peer pressure, online store appeal, acceptable prices, ease of business transactions, simple payment methods, and reduced prices so that consumers prefer to buy online (Srivastava & Thaichon, 2022). The consumer goods market is proliferating, with significant growth in the number of information media and competitive products (Mizuno et al, 2021). In everyday life, online shopping for consumer goods is growing, and the majority of women who buy consumer goods see it as a necessity, with 41% describing it as an -unavoidable obligation, without importance‖ (Pernot, 2021).…”
Section: Introductionmentioning
confidence: 99%